2012
DOI: 10.1007/s00167-012-2333-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo kinematics comparison of fixed- and mobile-bearing total knee arthroplasty during deep knee bending motion

Abstract: The present results demonstrated that the fixed-bearing and mobile-bearing posterior-stabilized designs had similar posterior condylar translation and tibial axial rotation during weight-bearing deep knee flexion exceeding 120°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 43 publications
0
10
1
Order By: Relevance
“…Shi et al [23] also reported that the mobile-bearing prosthesis caused medial and lateral condyle rollback during deep knee flexion, which is different from the kinematics of the mobile-bearing prosthesis in the present study. An LCS mobile-bearing prosthesis has characteristic features, including high congruency without the cam-post mechanism, whereas the PFC-Sigma RP-F mobile-bearing prosthesis has the cam-post mechanism.…”
Section: Discussioncontrasting
confidence: 91%
“…Shi et al [23] also reported that the mobile-bearing prosthesis caused medial and lateral condyle rollback during deep knee flexion, which is different from the kinematics of the mobile-bearing prosthesis in the present study. An LCS mobile-bearing prosthesis has characteristic features, including high congruency without the cam-post mechanism, whereas the PFC-Sigma RP-F mobile-bearing prosthesis has the cam-post mechanism.…”
Section: Discussioncontrasting
confidence: 91%
“…In vivo, posterior condylar translation and tibial axial rotation in flexion have been shown to be similar in patients with MB-TKA and FB-TKA [26]. For function [7][8][9][10], radiological outcome [8,11] and quality of life [7] generally no significant differences between both types of TKA were reported, although one meta-analysis did find lower pain scores in MB-TKA [27].…”
Section: Discussionmentioning
confidence: 99%
“…Relative orientation was defined using Euler angles (Z-X-Y sequence; flexion/extension, abduction/adduction, external/internal rotation) based on custom Matlab scripts. This process has shown to be reliable and good intra-class agreement (ICC: 0.94–0.96) (Shi et al 2014). …”
Section: Methodsmentioning
confidence: 99%